Interactions during co-pyrolysis of direct coal liquefaction residue with lignite and the kinetic analysis. (1st March 2018) - Xu, Junli; Bai, Zongqing; Li, Zheng; Guo, Zhenxing; Hao, Pan; Bai, Jin; Li, Wen
Highlights: Positive and negative interactions are co-existing during co-pyrolysis of DCLR with lignite. HS and A in DCLR promote the release of volatiles at low temperatures during co-pyrolysis. The pyrolysis reactivity of co-pyrolysis samples increases with the increase of DCLR fraction. Abstract: Co-pyrolysis process of direct coal liquefaction residue (DCLR) with lignite was examined by thermogravimetric analyzer (TGA) and the kinetic characteristics were analyzed using Kissinger-Akahira-Sunose method. And different mass ratios of DCLR to lignite (10:0, 8:2, 6:4, 4:6, 2:8 and 0:10) were considered in this work. At the same time the influences of individual components in DCLR on co-pyrolysis process were investigated as well. Results showed that significant difference presented in experimental and calculated co-pyrolysis curves of DCLR with lignite. And such difference was related to pyrolysis temperature and mixed ratio of sample. The volatiles yield increased (experimental volatiles yield > calculated one) for the co-pyrolysis of DCLR with lignite at low temperatures (200–500 ○ C) while decreased at high temperatures (experimental volatiles yield < calculated one, 500–900 ○ C), and with the addition of DCLR, such increasement of volatile yield at low temperatures was weakened whereas the decrement at high temperatures was strengthened. The increase of volatiles of co-pyrolysis samples at low temperatures was ascribed to the heavy oils and asphaltenes in DCLR whereas all the individual fractions in DCLR could result in the decrease of volatile yield at high temperatures. And the activation energies of co-pyrolysis samples of lignite with DCLR decreased with the increase of DCLR dosage, which indicated that the co-pyrolysis reactivity of mixed samples increased gradually.